The genetic location and regulation of aminoglycoside resistance genes in acinetobacter - Segal, Heidi (Division of Medical Microbiology, 2017)
The genetic basis of aminoglycoside resistance in clinical isolates of Acinetobacter was investigated. The aadB genes cloned from two clinical isolates, strain CHA and strain SUN, were sequenced. Analysis of the sequencing data indicated that both genes were contained on gene cassettes, which had integrated at secondary sites on a plasmid isolated in each strain. Gene cassettes are usually associated with integrons, and cassettes recombined at secondary sites are thought to be stably integrated. However, conduction assays indicate that the aadB gene cassette described in this study is potentially mobile. Outside of an integron, transcription of the structural gene on a cassette is dependent on insertion of the cassette downstream of correctly aligned promoter sequences. A number of putative promoters were identified upstream of the aadB structural gene. Primer extension studies were carried out to study the regulation of aadB. These experiments showed that in Acinetobacter the aadB gene is regulated by a promoter consisting of a -10 hexamer only. Similar experiments showed that, in Escherichia coli, the same gene is transcribed from a different promoter, which is typical of those recognized by the major RNA polymerase in this organism. Thus, the transcription signals recognized in Escherichia coli were different from those recognized in Acinetobacter. Naturally occurring plasmids in clinical isolates of Acinetobacter have not been fully characterized: pRAY was characterized by sequencing. An analysis of the sequencing data identified features consistent with an origin of replication. Moreover, this analysis suggests that pRAY may be mobilizable. This work, in part, has been published in FEMS Microbiology Letters (Segal and Elisha, 1997).